Solve for y 12/(y-1)=2/3

Math
12y-1=23
Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.
12⋅3=(y-1)⋅2
Solve the equation for y.
Tap for more steps…
Rewrite the equation as (y-1)⋅2=12⋅3.
(y-1)⋅2=12⋅3
Multiply 12 by 3.
(y-1)⋅2=36
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in (y-1)⋅2=36 by 2.
(y-1)⋅22=362
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
(y-1)⋅22=362
Divide y-1 by 1.
y-1=362
y-1=362
Divide 36 by 2.
y-1=18
y-1=18
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 1 to both sides of the equation.
y=18+1
Add 18 and 1.
y=19
y=19
y=19
Solve for y 12/(y-1)=2/3

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top